The sociopolitical impacts of the english first movement: language policy, identity, and exclusion in the united states - Moehamad Sandy Hermawan; Nur Iman Subono (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study explores how the English-only movement, particularly through the agenda of the English First campaign, has influenced U.S. public policy in ways that impact non-English-speaking communities. Grounded in New Social Movement and Dominant Culture theories, the research employs a conceptual and document-based approach to analyze five key cases: California’s Proposition 227, Arizona’s Proposition 203, Executive Order 14224, EEOC v. Premier Operator Services, and language challenges in Aurora, Colorado schools. These cases reveal how English-only ideologies have been codified into educational, legal, and workplace policies that marginalize linguistic minorities and reinforce English as a marker of national identity. While often framed as promoting unity or efficiency, these policies have limited access to public services, equitable schooling, and fair employment for immigrant communities. Rather than measuring policy outcomes quantitatively, the study highlights the symbolic and structural dimensions of language governance, underscoring the need for inclusive, multilingual policies that protect linguistic rights and democratic participation in the U.S.